UPAYA PEMBERDAYAAN MASYARAKAT UNTUK PRODUKSI ABON JAMUR TIRAM SEBAGAI PELUANG USAHA - Nurzihan, Nastitie Cinintya (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2022)
Food has an important role for health, food quality can be viewed from the aspect of quality, nutritional content and health. Development and growth that is fast and relatively low cost makes it easy for oyster mushrooms to be cultivated. Processing of oyster mushrooms into shredded products is an alternative to plant-based food, such as shredded oyster mushrooms is done with simple technology that can be applied at the household level and as food products with lower prices, delicious and healthy flavors. Mushroom processing that does not vary is actually one of the causes that have not been used optimally, for that this community service is carried out with the aim of developing processed oyster mushroom products and can be continued as a small and medium business. Community service activities in the form of community empowerment efforts for the production of oyster mushrooms as a business opportunity were attended by 40 participants by providing materials, demonstrating and presenting books, showing high enough results with a percentage of 85% and also based on monitoring and evaluation it was found that 50% of participants who participated in the activity of repeating the production of shredded oyster mushrooms and as many as 5% of participants carried out the business of shredded oyster mushrooms. Keywords: diversification; oyster mushroom; business opportunity